Aspek Farmakologi dan Perilaku Hidup Bersih dan Sehat di Panti Asuhan Muhammadiyah - Febrina Dewi Pratiwi Lingga; Ratih Yulistika Utami; Hervina Hervina (CERED Indonesia Publishing, 2021)
Scabies is often neglected because it is not life-threatening and therefore the priority for treatment is low, however, chronic and severe scabies can cause dangerous complications. The aim of this research is to increase the understanding and skills of orphanage students and guardians of the Muhammadiyah Boys orphanage Branch Head of Muhammadiyah Medan City regarding skin diseases related to environmental cleanliness and their initial handling, and to motivate orphanage students to always maintain the cleanliness of the orphanage environment. Training and counseling with the method of lectures, discussions, and demonstrations of early management of skin diseases related to environmental health. In addition, there is a role play clean action with all the orphanage students. Empowerment of orphanage students and guardians is needed in an effort to prevent skin diseases related to environmental hygiene. After this activity, the students realized the importance of keeping the environment clean and motivated to keep the environment clean, so that the orphanage environment became cleaner and more orderly. Students are also able to do initial management of skin diseases related to environmental hygiene and students who suffer from skin diseases have mostly been overcome. Clean and healthy lifestyle (PHBS) need to be applied so that students avoid skin diseases related to environmental cleanliness and its complications.